Analisis Perubahan Pemanfaatan Ruang Terbuka Hijau di Kecamatan Mandai Kabupaten Maros - Rudi Latief; Yudistira Taufiq Hidayat; Ilham Yahya (Fakultas Teknik Universitas Bosowa, 2021)
The purpose of this study is to find out what causes changesin the use of Green Open Space (RTH) in Mandai District, MarosRegency and to find out how to control changes in the use of GreenOpen Space (RTH) in Mandai District. The variables used consist ofsix variables, namely; Topography, Population, Land Value,Accessibility, Facilities and Infrastructure, and Land CarryingCapacity;. The analytical method used is chi-square analysis.Furthermore, it describes efforts to control changes in the use of greenopen space (RTH) in Mandai District, Maros Regency usingdescriptive analysis methods. The variable that has a moderateinfluence on changes in the use of green open space (RTH) in Mandaisub-district, Maros regency, is the population variable so that effortsto control changes in the use of green open space (RTH) are equitabledevelopment, service to the community so that there is no explosion andexcessive population mobility. Minister of Public Works RegulationNo. 5 of 2008 concerning Guidelines for Provision and Utilization ofGreen Open Space in Urban Areas. Also referring to Law no. 26 of2007 concerning spatial planning. As the provision of 30% Green OpenSpace (RTH) of the total area